THE INFLUENCE OF EARNING PER SHARE AND RETURN ON ASSETS ON THE COMPANY VALUE OF PT RAMAYANA LESTARI SENTOSA TBK - Iriana Kusuma Dewi (International Journal Multidisciplinary Science, 2024)
This research aims to test whether earnings per Share and Return On Assets influence the Company Value of PT Ramayana Lestari Sentosa Tbk for the 2011-2022 period partially or simultaneously. The research method used is causal associative research with a quantitative approach. The population of this research is the financial report data of PT Ramayana Lestari Sentosa Tbk for 2011-2022. Data analysis was done using multiple linear regression analysis with the help of the Statistical Package for Social Science (SPSS) version 26 program. The research results show that EPS partially does not significantly influence company value. Likewise, Return On Assets partially does not have a significant effect on Company Value. Simultaneously, earnings per Share and Return On Assets do not significantly affect Company Value at PT Ramayana Lestari Sentosa Tbk for the 2011-2022 period. The coefficient of determination shows that the Adjusted R Square value is 0.277 or 27.7% of the variation in Company value, which can be explained by independent variables, namely Earning Per Share and Return On Assets, the remaining, around 72.3% of the variation in Company value is influenced by factors- other factors not included in the regression model